PRAGMATICS, PLURILINGUALISM, AND LANGUAGE DOMINANCE IN ENGLISH RUSSIAN UZBEK MEDIA CONTEXTS - Satibaldiev Erkinjon (Modern American Journals, 2025)
This article examines how pragmatic factors and asymmetric language power shape the translation of contemporary media texts among English, Russian, and Uzbek. Drawing on current scholarship in translation studies, pragmatics, and Central-Asian sociolinguistics, it argues that successful mediation across these three languages demands a fine balance between global English influence, the residual prestige of Russian, and the growing identity-building role of Uzbek. A qualitative synthesis of recent literature shows that translators negotiate this tri-polar hierarchy through flexible localisation, selective retention of loanwords, and culturally embedded pragmatic moves that secure communicative equivalence. Recommendations for translator education and future research conclude the discussion.
Keywords: Pragmatics, plurilingualism, language dominance, media translation, English, Russian, Uzbek, localisation